Effect of Temperature on Dynamic Fracture Toughness of Rock - Gong, Nengping (Asian Journal of Chemistry, 2014)
In order to study the effect of temperature on fracture properties of rock materials, the stress impulse are controlled to achieve the relationship of average load, time and temperature by changing the testing temperature. According to the basic test method for fracture toughness of specimen, we test the specimens on split Hopkinson pressure bar system and calculate the fracture toughness. The test results indicated that when the temperature increases from 10 to 100 ºC, the fracture toughness of rocks reduce steadily.